Unusual strain relaxation mechanism in metastable β Ti-Nb alloy after rapid solidification. (1st April 2022) - Lin, Wenhao; Heinrich, Helge; Ma, Ji
Abstract: In this study, an unusual structural distortion in metastable β Ti-Nb was observed after laser melting. Selected area diffraction patterns (SADPs) from transmission electron microscopy (TEM) reveal that after rapid solidification from laser scans in a Ti-25Nb (at.%) sample, a difference in crystal structure was observed between the cellular solidification interior and the intercellular regions. While the intercellular regions remained the bcc (β) phase, the structure of the cell interior dis not match either β or the α'' martensite. Instead, this structure can be interpreted either as an ordered orthorhombic structure with significantly different lattice parameters compared to α'', or a distorted β with 8% strain along with one of the < 100 > β directions with selected variants of nanodomains which originate from the relaxation of interstitial oxygen atoms. Graphical abstract: Image, graphical abstract